Ketyl Radical Enabled Synthesis of Oxetanes - Gatazka, Michael R.; Parikh, Seren G.; Rykaczewski, Katie A.; Schindler, Corinna S. (Synthesis, 2024)
Oxetanes, 4-membered oxygen-containing heterocycles, were identified to have pharmaceutical applications after the discovery of the chemotherapeutic drug taxol (Paclitaxel) and its analogues. Furthermore, oxetanes have been identified as bioisosteres for several common functional groups and are present in a number of natural products. However, oxetanes are one of the least common oxygen-containing heterocycles in active pharmaceutical ingredients on the market, which can be attributed, in part, due to challenges with their synthesis. Previous strategies rely on nucleophilic substitutions or [2+2]-cycloadditions, but are limited by the stepwise buildup of starting material and limitations in scope resulting from requirements for activated substrates. To address these limitations, we envisioned activating simple carbonyls to their corresponding α-oxy iodides to promote ketyl radical formation. These radicals can then undergo atom-transfer radical addition with alkenes followed by one-pot nucleophilic substitution to produce oxetanes. Herein, we present a proof-of-principle of this strategy in which fluoroalkyl carbonyls are successfully converted into the corresponding fluoroalkyl oxetanes.
Keywords: oxetane; ketyl radical; visible light; photochemistry; α-oxy halide; atom-transfer radical addition